Head-to-Head Comparison of Different Blood Collecting Tubes for Quantification of Alzheimer’s Disease Biomarkers in Plasma - Lijun Jiang; Xulong Ding; Wenxiao Wang; Xiaobin Yang; Tao Li; Peng Lei (Biomolecules, 2022)
To examine whether the type of blood collection tubes affects the quantification of plasma biomarkers for Alzheimer’s disease analyzed with a single-molecule array (Simoa), we recruited a healthy cohort (n = 34, 11 males, mean age = 28.7 ± 7.55) and collected plasma in the following tubes: dipotassium ethylenediaminetetraacetic acid (K2-EDTA), heparin lithium (Li-Hep), and heparin sodium (Na-Hep). Plasma tau, phosphorylated tau 181 (p-tau181), amyloid β (1–40) (Aβ40), and amyloid β (1–42) (Aβ42) were quantified using Simoa. We compared the value of plasma analytes, as well as the effects of sex on the measurements. We found that plasma collected in Li-Hep and Na-Hep tubes yielded significantly higher tau and p-tau181 levels compared to plasma collected in K2-EDTA tubes from the same person, but there was no difference in the measured values of the Aβ40, Aβ42, and Aβ42/40 ratio. Therefore, the type of blood collecting tubes should be considered when planning studies that measure plasma tau.